2002
DOI: 10.1101/gad.1039602
|View full text |Cite
|
Sign up to set email alerts
|

Complex transcriptional circuitry at the G1/S transition in Saccharomyces cerevisiae

Abstract: In the yeast Saccharomyces cerevisiae, SBF (Swi4-Swi6 cell cycle box binding factor) and MBF (MluI binding factor) are the major transcription factors regulating the START of the cell cycle, a time just before DNA replication, bud growth initiation, and spindle pole body (SPB) duplication. These two factors bind to the promoters of 235 genes, but bind less than a quarter of the promoters upstream of genes with peak transcript levels at the G1 phase of the cell cycle. Several functional categories, which are kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
198
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 245 publications
(202 citation statements)
references
References 55 publications
(79 reference statements)
3
198
0
1
Order By: Relevance
“…4G). This conclusion holds, independent of whether SBF and MBF targets are defined based on evolutionary analysis of conserved binding sites in 17 related fungus species or on various experimental studies (29,30).…”
Section: Timingmentioning
confidence: 79%
“…4G). This conclusion holds, independent of whether SBF and MBF targets are defined based on evolutionary analysis of conserved binding sites in 17 related fungus species or on various experimental studies (29,30).…”
Section: Timingmentioning
confidence: 79%
“…4A) than RFA1, which is activated by the downstream factor Yhp1p (35). We investigated the RPA example further, and found that Rfa1 protein levels were comparable in cdc14 and cdc15 strains (Fig.…”
Section: G1 Transcription and Nuclear Import Defects In Cdc14 Impairmentioning
confidence: 99%
“…For tree species that are amenable to genetic transformation, methods are technically demanding and slow, requiring 12 to 18 months of tissue culture (Merkle and Dean, 2000). To reveal a functional hGRN for wood formation, an efficient transgenic system, such as those developed for the cell cultures of yeast (Saccharomyces cerevisiae) and animals (Horak et al, 2002;Yu and Gerstein, 2006;Gerstein et al, 2010;Cheng et al, 2011;Niu et al, 2011), is needed where immediate transcriptome responses to TF perturbation can be induced, characterized, and quantified.…”
Section: Introductionmentioning
confidence: 99%